Developing an occupational health service for health professionals: Management challenges. (2nd October 2021) - Hossain, Md Shamim; Khan, Mohammad Jamal; Yahya, Sofri B.
ABSTRACT: Currently, research on health supervision service and physicians' wellbeing has grown rapidly. However, the literature on health supervision service and physicians' wellbeing and service attachment are scarce especially in the context of Bangladesh. A quantitative study was performed and the data were collected using the purposive sampling method. A survey was performed among 192 physicians from different public and private hospitals in Bangladesh. The data were analysed using the structural equation modelling (SEM) by partial least square (PLS) approach using SmartPLS 3.2.8. This study has found a significant positive relationship between health supervision service and physicians' wellbeing ( p < 0.01). Besides, physicians' wellbeing was found to have a positive influence on their service attachment ( p < 0.01). The study provides inputs to the policymakers in formulating policies in the development of Bangladesh's health sector and health supervision service. However, with limitations, the generalizability of the study results needs attention due to the unavailability of the sample frame.